Descrição da camada limite atmosférica sobre o Oceano Atlântico sudoeste através de dados observacionais - Rossato, Fernando (2015)
Between 3-12 December 2012, the Oceanographic Vessel Alpha Crucis held oceanographic stations in the Southwestern Atlantic Ocean in support to both SAMOC (South Atlantic Meridional Overturning Circulation) and ACEx (Atlantic Ocean Carbon Experiment) projects. During the research cruise, the vessel performed 19 measurements with the release of weather balloons with radiosondes. From the data collected by the radiosondes, it was possible to verify the variability of the marine atmospheric boundary layer (MABL) over different synoptic conditions occurring in the area and period of study. From meteorological and oceanographic data collected throughout the trajectory of the ship by an automatic weather station and the onboard termosalinograph, it was possible to estimate the latent and sensible heat fluxes between the ocean and the atmosphere from bulk parameterization. In order to better understand the importance of the local forcing mechanisms imposed by the sea surface temperature (SST) and the large-scale forcing by the current synoptic conditions in the study period, 19 measurements were divided into four transects along the complete ship's trajectory, where the data were grouped with respect to the active synoptic weather conditions in the study area. Our results demonstrate that in the absence of large-scale transient systems acting in the study area, the MABL was modulated by the SST field. This was observed in the first transect, were we found a thick and turbulent MABL with its top at around 600 m and more intense heat fluxes (up to 209 W/m² of latent heat and 47 W/m² of sensible heat) mainly over the warm waters associated with the Brazil Current (BC). Over cooler waters of the transect, outside the domain of the BC, the MABL was shallower, around 200 m, with less intense heat fluxes (up to 1.4 W/m² of latent heat and -16.8 W/m² of sensible heat). In the second transect with the formation of an extratropical cyclone in the La Plata river mouth region, we noted the impact of the synoptic atmospheric conditions influencing the evolution of the MABL during the prefrontal condition when a MABL stratification was verified. During the pos frontal situation, the MABL was a well developed one, with a 1200 m height. In the pos frontal environment, latent heat fluxes (average 290 W/m² with a peak of 468 W/m²) and sensible heat fluxes (average of 18 W/m² with a peak of 45 W/m²) indicate a heat flux directed from the ocean to the atmosphere much more intense in his latent component. On the other hand, in the prefrontal region, lower values of the latent heat fluxes (average of 18 W/m² with a minimum of 15.8 W/m²) and sensible heat fluxes (-63.4 W/m²) were found. During the third transect with the incursion of the warm air mass, the MABL became shallower over the cooler waters of the Brazilian Coastal Current. Along of the entire third transect the SST was lower than the air temperature and this transect presented a stable boundary layer. Throughout the fourth and final transect, there was a secondary cyclogenesis off the coast of the Rio Grande do Sul state in southern Brazil, just north of the cyclone that has been formed in the vicinity of the La Plata river mouth. This cyclone has developed rapidly and has moved toward the Southwestern Atlantic Ocean, leaving the study area in the cold sector of the cyclone. With the incursion of the cold air mass, the MABL become thicker and more turbulent with its top around 600 m. The values of latent heat fluxes ranged between 461.2 W/m² over the warm waters associated with the BC and 30.2 W/m² on the cooler waters outside the domain of the BC. This work offers an analysis of movel meteorological and oceanographic observations taken simultaneously in the Southwestern Atlantic Ocean. These observations are fundamental to widen our understanding on the physical processes occurring at the ocean-atmosphere interface and have primary importance for the weather and climate forecast of the south-southwestern region of Brazil.